Adsorptive Purification of Ionic Liquids and their Reuse in Cellulose Processing. Issue 12 (6th November 2017) - Watts, Marcus; Kosan, Birgit; Hammerschmidt, Jochen; Dorn, Susann; Meister, Frank; Scholl, Stephan
Abstract: Unfortunately, imidazole‐based ionic liquids (ILs) tend to build high‐boiling impurities like chromophores. This results in reduced process stability and product conditions like stained cellulose fibers. Therefore, different adsorbent materials were tested for their capability to purify the IL 1‐ethyl‐3‐methylimidazolium acetate. The product quality was monitored by UV‐vis spectroscopy. It was observed that activated carbon showed the best purification results. The purified IL was successfully reused in the process of cellulose dissolution and shaping. Abstract : A purification process for discolored imidazole‐based ionic liquids (ILs) for the use in cellulose processing is presented. UV‐vis spectroscopy revealed that activated carbon is the best suitable adsorbent material for reducing the discoloration in ILs. Furthermore, IL properties do not alter during purification for cellulose processing.